The Effect of Project-Based Learning on Student Motivation and Collaboration in Science (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Project-based learning is a fairly new teaching strategy that is being used today. This strategy includes the use of projects to create an immersive environment for students to learn. Students are involved in the material and are required to use critical thinking skills to solve the problems given by the teacher. Students in the science classroom can often become disengaged in the material and project-based learning can be used to help increase motivation. This article discusses the positives to incorporate project-based learning in the classroom and how project-based learning increases student motivation and collaboration in the classroom.
Keywords: science; project-based learning; education